Penerapan Teori Behavior Dengan Teknik Self-Management Untuk Mengatasi Kurangnya Manajemen Waktu Pada Mahasiswa - Rofiq, Arif Ainur; Rahayu, Septyana Dwi; Laela, Faizah Noer (Jurusan Bimbingan dan Konseling Islam, 2023)
The focus of this research is: 1. What is the condition of the counselee before the Application of Behavior Theory by Using Self-Management Techniques to Overcome Lack of Time Management in College Student? 2. What is the process of applying Behavior Theory by Using Self-Management Techniques to Overcome Lack of Time Management in College Student? 3. What is the impact of the Application of Behavior Theory by Using Self-Management Techniques to Overcome the Lack of Time Management in College Student?. To be able to answer these problems, in the research above, this study used descriptive qualitative research methods. The data collection techniques are interviews, field observations which have been described in the data presentation chapter. The implementation process is based on the five-step counseling process, namely: problem identification, diagnosis, prognosis, treatment or therapy, evaluation and follow-up. The end result of this study is that after carrying out the counseling process and applying behavior therapy with self-management techniques, there is a change in the counselee's behavior. These changes can be seen from the counselee who is able to control himself and manage his time well. These changes are seen gradually after the treatment process is applied